Real life clinical outcomes of relapsed/refractory diffuse large B cell lymphoma in the rituximab era: The STRIDER study - Irene Dogliotti; Veronica Peri; Michele Clerico; Francesco Vassallo; Davide Musto; Silvio Mercadante; Simone Ragaini; Barbara Botto; Mario Levis; Mattia Novo; Marco Ghislieri; Luca Molinaro; et al. (Cancer Medicine)
Abstract Background Relapse and refractory (R/R) rates after first‐line R‐CHOP in diffuse large B cell lymphomas (DLBCL) are ~40% and ~15% respectively. Aims We conducted a retrospective real‐world analysis aimed at evaluating clinical outcomes of R/R DLBCL patients. Material and Methods Overall, 403 consecutive DLBCL patients treated in two large hematological centers in Torino, Italy were reviewed. Results At a median follow up of 50 months, 5‐year overall survival from diagnosis (OS‐1) was 66.5%, and 2‐year progression free survival (PFS‐1) was 68%. 134 (34.4%) patients relapsed (n = 46, 11.8%) or were refractory (n = 88, 22.6%) to R‐CHOP. Most employed salvage treatments included platinum salt‐based regimens in 38/134 (28.4%), lenalidomide in 14 (10.4%). Median OS and PFS after disease relapse or progression (OS‐2 and PFS‐2) were 6.7 and 5.1 months respectively. No significant difference in overall response rate, OS‐2 or PFS‐2 in patients treated with platinum‐based regimens versus other regimens was observed. By multivariate analysis, age between 60 and 80 years, germinal center B cell type cell of origin and extranodal involvement of <2 sites were associated with better OS‐2. Discussion Our findings confirm very poor outcomes of R/R DLBCL in the rituximab era. Widespread approval by national Medicine Agencies of novel treatments such as CAR‐T cells and bispecific antibodies as second‐line is eagerly awaited to improve these outcomes.